2022
DOI: 10.3390/app12168138
|View full text |Cite
|
Sign up to set email alerts
|

Varroa Control by Means of a Hyperthermic Device

Abstract: Hyperthermia is the use of heat to control Varroa destructor. Various apparatuses have been proposed to effectively apply heat and recently the Bee Ethic system was developed in Italy. The Bee Ethic system is a technological hive consisting of a set of heated frames and an electronic control unit. Trials were carried out in the years 2018, 2020 and 2021 to compare colony strength and mite infestation in heat-treated and untreated control bee-hives. In addition, the influence of repeated heat treatments on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…However, it can be noted here that there are several heat shock proteins involved in proteostasis, and our study did not measure the capacity of bees to handle heat stress. Bees are known to have a slightly higher tolerance to high temperatures compared to Varroa mites, but it is also likely that this small beneficial impact could become minimal over an extended time as the parasite adapts to changing environmental conditions [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it can be noted here that there are several heat shock proteins involved in proteostasis, and our study did not measure the capacity of bees to handle heat stress. Bees are known to have a slightly higher tolerance to high temperatures compared to Varroa mites, but it is also likely that this small beneficial impact could become minimal over an extended time as the parasite adapts to changing environmental conditions [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cournoyer et al [11] demonstrated that continued and severe exposure to varroa leads to increased viral charges and decreased sugar concentrations in haemolymphs, with possible alterations in immunity, metabolism, and reserve mobilization. Porporato et al [12] developed the Bee Ethic system to apply hyperthermia in order to control V. destructor, using an integrated pest management (IPM) approach without chemicals. Smodiš Škerl et al [13] recorded the efficacy of VarroMed ® against V. destructor in different climatic conditions, ranging from 71.2 to 89.3% in the summer/autumn and from 71.8 to 95.6% in the winter.…”
mentioning
confidence: 99%